High-Pressure-Based Strategies for the Inactivation of Bacillus subtilis Endospores in Honey - Hana Scepankova; Carlos A. Pinto; Letícia M. Estevinho; Jorge A. Saraiva (Molecules, 2022)
Honey is a value-added product rich in several types of phenolic compounds, enzymes, and sugars recently explored in biomedical and food applications. Nevertheless, even though it has a low water activity (aW ≈ 0.65) that hinders the development of pathogenic and spoilage microorganisms, it is still prone to contamination by pathogenic microorganisms (vegetative and spores) and may constitute harm to special groups, particularly by immunosuppressed people and pregnant women. Thus, an efficient processing methodology needs to be followed to ensure microbial safety while avoiding 5-hydroxymethylfurfural (HMF) formation and browning reactions, with a consequent loss of biological value. In this paper, both thermal (pressure-assisted thermal processing, PATP) and nonthermal high-pressure processing (HPP), and another pressure-based methodology (hyperbaric storage, HS) were used to ascertain their potential to inactivate Bacillus subtilis endospores in honey and to study the influence of aW on the inactivation on this endospore. The results showed that PATP at 600 MPa/15 min/75 °C of diluted honey (52.9 °Brix) with increased aW (0.85 compared to ≈0.55, the usual honey aW) allowed for inactivating of at least 4.0 log units of B. subtilis spores (to below detection limits), while HS and HPP caused neither the germination nor inactivated spores (i.e., there was neither a loss of endospore resistance after heat shock nor endospore inactivation as a consequence of the storage methodology). PATP of undiluted honey even at harsh processing conditions (600 MPa/15 min/85 °C) did not impact the spore load. The results for diluted honey open the possibility of its decontamination by spores’ inactivation for medical and pharmaceutical applications.